(untitled) (NEW: Emerging scholars in Australian Indigenous Studies, 2019)
Eurocentric conceptions of Indigenous history have long dominated the conversation around what constitutes ‘legitimate’ Aboriginality. This essay examines the hyper-scrutiny Aboriginal art and oral history forms are subject to, as well as the continual omission and manipulation of Aboriginal history as a reflection of the ongoing colonial process. Keywords oral history; Indigenous art; the colonial gaze